Multifunctional inorganic biomaterials: New weapons targeting osteosarcoma - Wang, Dong; Peng, Yi; Li, Yuezhan; Kpegah, Julius K. S. K.; Chen, Shijie (Frontiers in Molecular Biosciences, 2023)
Osteosarcoma is the malignant tumor with the highest incidence rate among primary bone tumors and with a high mortality rate. The anti-osteosarcoma materials are the cross field between material science and medicine, having a wide range of application prospects. Among them, biological materials, such as compounds from black phosphorous, magnesium, zinc, copper, silver, etc., becoming highly valued in the biological materials field as well as in orthopedics due to their good biocompatibility, similar mechanical properties with biological bones, good biodegradation effect, and active antibacterial and anti-tumor effects. This article gives a comprehensive review of the research progress of anti-osteosarcoma biomaterials.